Association between psychological symptoms in adults and growth in early life: longitudinal follow up study. Issue 7367 (5th October 2002) - Cheung, Y B; Khoo, K S; Karlberg, J; Machin, D
Abstract: Objectives: To test the hypothesis that birth weight for gestational age and weight gain in early childhood have a long term association with psychological distress in adults. Design: Longitudinal study of 1958 birth cohort followed to age 42 years. Setting: Population based birth cohort study. Participants: 9731 cohort members with valid perinatal, postnatal, and adult data. Main outcome measures: Malaise inventory scores measured at ages 23, 33, and 42 years. Generalised estimating equations approach used to analyse repeated measures. Results: Psychological distress score was inversely related to birthweight z score and weight gain from birth to the age of 7 years. A unit increase in birthweight z score or childhood weight gain was associated with a mean reduction in psychological distress score of 0.10 (95% confidence interval 0.05 to 0.15) and 0.06 (0.02 to 0.10), respectively. Birth weight and weight gain were also inversely related to the odds of having a high level of psychological distress, with odds ratios being 0.90 (0.85 to 0.95) and 0.93 (0.89 to 0.98), respectively. Conclusions: Psychological health in adults is related to fetal growth and growth in early childhood.